The Bhutto Dynasty and the Pakistan People’s Party: Populism, Power, and Tragedy - Asifa Zafar; Dr. Farhat Nasim (Journal of Religion and Society, 2026)
This article examines the Bhutto dynasty and the Pakistan People's Party (PPP) as a central paradox in Pakistani politics, tracing their evolution from Zulfikar Ali Bhutto's 1967 founding of the party amid anti-establishment populism to its contemporary role under Bilawal Bhutto Zardari. It analyzes how the PPP's left-leaning ideology, encapsulated in "Roti, Kapra, Makaan," mobilized masses against elite and military dominance, delivering landmark achievements like the 1973 Constitution and women's rights advancements under Benazir Bhutto, while grappling with authoritarian drifts, corruption allegations, dynastic succession, and recurrent tragedies including executions, assassinations, and coups that have shaped Pakistan's turbulent democratic trajectory. The study highlights the party's shift from revolutionary populism to pragmatic coalition politics, regional entrenchment in Sindh, and efforts at revival amid military influence and declining national appeal. Ultimately, it argues that the Bhutto-PPP saga embodies both inspiration for progressive resistance and a cautionary tale of how charismatic mobilization, intertwined with familial control and praetorian structures, impedes consolidated democracy, underscoring the need for institutionalized parties beyond dynastic legacies to foster sustainable civilian rule and social equity in Pakistan. Keywords: Bhutto Dynasty, Pakistan People's Party, Political Populism, Dynastic Politics, Civil-Military Relations, Democratic Tragedy